"Double-edged sword" of Digital Media Use among Youth in Residential Treatment: Perspectives of Service Providers. Issue 2 (3rd April 2021) - Good, Bethany; Mishna, Faye
ABSTRACT: The social significance of digital media and technology is incontestable, particularly with youth. While digital media use can offer youth in residential treatment (RT) opportunities, it also carries risks. Although there has been a shift in RT from a model fostering isolated, self-contained settings, toward the promotion of family and community integration, there is a dearth of scholarship addressing youth digital media use in RT. To address the gaps in research on digital media use among youth in RT and the absence of system-wide policies and formal consensus on guidelines for addressing the issue, the findings of the current study offer insight into the experiences of 25 service providers from four programs. The findings highlight that regardless of location or treatment approach, RT is addressing youth digital media use. There exists a continuum of approaches ranging from risk prevention to risk resilience. As social media have made prohibiting contact between youth impossible, digital media use has been a catalyst for programs to attend to youth relationships outside of the programs. Digital media have thus both introduced new challenges to supporting youth and facilitated a more contemporary resilience-oriented and ecologically informed the approach to treatment.